Alpha-angelica lactone catalyzed oxidation of pyrrolidines to lactams - Deepake, Siddharth K.; Kumar, Manish; Kumar, Pawan; Das, Utpal (European Journal of Organic Chemistry, 2022)
Herein, we report an efficient protocol for the synthesis of gamma-lactams from pyrrolidines and oxygen. The strategy follows a two-step process involving an initial generation alpha-amino alkyl radicals from pyrrolidines and oxygen in presence of 4-dimethylaminopyridine (DMAP) followed by trapping of the radical with oxygen species. This protocol demonstrates good functional group acceptance and provides a direct method to access gamma-lactams. The lactam derivatives were obtained in up to 98 % yield.
Keywords: alpha-Amino alkyl radicals; alpha-Angelica lactone; lactams; Oxidation; Pyrrolidines